657 Low back pain- Algorithm of diagnosis and management (Balneo and PRM Research Journal, 2024)
Introduction: Low back pain is a frequent condition, associated as a symptom with a multitude of organic or non-organic pathologies, resulting in the appearance of disability generating negative economic and soc-professional consequences. Being a relatively common symptom among patients, we created this paper with the aim to high-light the importance of the clinical examination along with the correct direction of the patient to a profile depart-ment, the review of differential diagnoses, as well as the establishment of a particular recovery plan adapted to each case.Materials and Methods: We analyzed a series of recent articles using the PubMed and the Cochrane Library data-bases ,using the keywords words “low back pain” and “rehabilitation”, to obtain data on the clinical and paraclinical examination, positive and differential diagnosis of chronic low back pain, as well as on rehabilitation management.Results: Low back pain may appear due to vertebral conditions (inflammatory, infectious, traumatic, neoplastic, degenerative, metabolic), or due to extravertebral causes. Along with the anamnesis, clinical examination and im-agistic investigations, we establish the positive diagnosis and create an individualised rehabilitation plan. The reha-bilitation protocol is divided into stages , the final goal is to minimize the ischemia-pain-contracture chain.Conclusion: The pathology of the lumbosacral spine can be characterized by the word "diversity", being one of the causes of early disability of the population in the field of work. Our work highlights the importance of the clinical and paraclinical examination in outlining the differential diagnosis of chronic lumbar pain, as well as the role of the multidisciplinary team in complex individualized rehabilitation treatment.